2016
DOI: 10.1186/s11671-016-1552-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanomaterials Based on Graphene and Gold Nanoclusters for Efficient Electrocatalytic Reduction of Oxygen

Abstract: Nanocomposites based on gold nanoclusters (AuNCs) with polyvinyl pyrrolidone as ligand and reduced graphene oxide (RGO) have been prepared and employed as efficient electrocatalysts for oxygen reduction reaction (ORR). AuNCs were synthesized through a wet chemical approach and then loaded onto the RGO. The as-prepared hybrid materials were pyrolyzed to remove the organic ligands. The composites were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…17,18 However, the size-specific catalytic activity of AuNCs has often been difficult to determine experimentally as clusters are prone to aggregation either during deposition or activation on the support, 19,20 or deactivation of the catalyst following initial reaction. 21 Therefore, methods for the fabrication of gold cluster-based catalysts resilient to aggregation are in high demand in nanomaterials, 22 catalysis 4,16,23,24 and sensing communities. 25,26 It has been shown that the successful deposition of AuNCs on surfaces depends on various factors, such as the type of support and ligand, synthetic conditions and cluster-support interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, the size-specific catalytic activity of AuNCs has often been difficult to determine experimentally as clusters are prone to aggregation either during deposition or activation on the support, 19,20 or deactivation of the catalyst following initial reaction. 21 Therefore, methods for the fabrication of gold cluster-based catalysts resilient to aggregation are in high demand in nanomaterials, 22 catalysis 4,16,23,24 and sensing communities. 25,26 It has been shown that the successful deposition of AuNCs on surfaces depends on various factors, such as the type of support and ligand, synthetic conditions and cluster-support interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that small metal nanoparticles (not size specific) such as Ag 27 , Pd 28 and Au, 21,29,30 can be immobilized on reduced graphene oxide (rGO). 31 rGO has a two-dimensional structure with extraordinary properties, such as high electrical conductivity, large surface area and high charge mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has also conducted some work regarding employing Au clusters based nanocomposite for ORR. We integrated polyvinyl pyrrolidone (PVP)-protected Au nanoclusters with reduced graphene oxide (RGO) as the catalyst [61] and found that the nanocomposite possessed markedly higher long-term stability in ORR than Pt/C. Subsequently, we fabricated nanocomposite based on p-mercaptobenzoic acid-functionalized Au nanoclusters, Au 102 (p-MBA) 44 , and porous carbon nanosheets [62].…”
Section: Au Clusters For Orrmentioning
confidence: 99%
“…In recent decades, sub-2 nm sized gold nanoclusters and complexes (AuNCs) have been explored as promising electrocatalysts for ORR, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] hydrogen evolution reaction (HER), [25] hydrogenation of terminal alkynes into alkenes, [26] CO oxidation, [27] styrene oxidation [28,29] and benzyl alcohol oxidation. [30,31] The unusual catalytic behaviour of the AuNCs compared to bulk Au is due to a series of size-dependant properties, including high surface-to-volume ratio, [15,32,33] molecular-like electronic properties, [34] and ligand density (if present).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that ligand removal is considered as a pathway to make more available active sites, it is challenging to retain the cluster size without ligands. [16][17][18][19][20][21][22][23][24] AuNCs ligands are typically organo-thiols or phosphines but can have a wide variety of organic functionality, which can alter the reactivity of AuNCs. [37] For instance, AuNCs protected by bulky ligands have lower ligand density, particularly at larger sizes, resulting in higher ORR activity compared to aliphatic and linear ligands.…”
Section: Introductionmentioning
confidence: 99%